Optimal Education with Mobile Capital. An OLG Approach - Jean-Marie Viaene; Itzhak Zilcha (Center for Economic Studies and ifo Institute (CESifo), 2000)
The paper considers a two-country model of overlapping generations economies with intergenerational transfers carried out in the form of bequest and investment in human capital. We examine in competitive equilibrium the optimal provision of education with and without capital markets integration. First, we explore how regimes of education provision - public, private or mixed - arise and how they affect the dynamics of autarkic economies. Second, we study the transitory and long-run effects of capital markets integration, in equilibrium, on the optimal provision of education and growth. Third, we examine a competition game where countries compete in the provision of public education.
Keywords: D90; E20; F20; J20; 330; Altruism; education; growth; human capital; capital markets integration